Review of technological developments and LCA applications on biobased SAF conversion processes - Borrill, Eleanor; Koh, S. C. Lenny; Yuan, Ruoyang (Frontiers in Fuels, 2024)
The aviation industry, driven by evolving societal needs, faces rising demand post-Covid and increasing pressure to align with emission reduction targets, prompting the development of drop-in sustainable aviation fuels (SAF). Their compatibility with existing aircraft and infrastructure will help to implement these fuels with the urgency the global climate crisis requires. This review delves into the benefits and challenges of various feedstocks, addressing complexities in estimating feedstock availability by location. Identified research gaps include enhancing feedstock availability, yield, and diversity, investigating compositions, and implementing sustainable agricultural practices. A summary of ASTM-certified conversion processes and technical specifications is outlined, prompting further research into conversion efficiency, catalyst selectivity, blending limits, aromatic compounds, combustion instability, and numerical modeling. A summary of recent life cycle assessments (LCA) highlighted gaps in cradle-to-cradle assessments, location-specific analyses, temporal considerations, and broader environmental impact categories. Recommendations stress obtaining primary data for enhanced LCA accuracy, conducting more specialized and general LCA studies and combining LCA, techno-economic analysis, fuel requirements, and socio-political assessments in multi-criteria decision analysis. This paper underlines the pressing need for comprehensive research to inform SAF production alternatives in the context of global climate crisis mitigation.